Building Knowledge across Language Systems: The Role of Audio and Visual Supports in Bilingual Learning through Self-Derivation - Alena G. Esposito; Katherine A. Lee; Brandan K. Gunarathne (MDPI AG, 2024)
Children who enter the US education system as emerging bilinguals (or English Learners) show significant gaps in test scores and graduation rates compared to their English monolingual peers. Dual-language education programs may provide an instructional context that capitalizes on emerging bilingual children's strengths and supports their academic performance while they acquire English. However, prior research has shown that integrating semantic knowledge across language systems poses a challenge. Supports may mitigate these challenges. Thus, across two studies, we examined instructional practices that may facilitate the integration of academic content across English and Spanish in elementary-age children enrolled in dual-language education programs. In Study 1, we examined whether facts presented through reading-while-listening or children's silent self-paced reading more effectively supported learning the facts and subsequent integration for dual-language students in grades 3 and 4 (n = 56; Mage = 9.54 years). In Study 2, we examined whether combining graphics with text was more effective in supporting fact learning and cross-language integration compared to facts presented as text alone in dual-language students in grades 4 and 5 (n = 67; Mage = 10.48 years). Overall, the studies replicate the benefits of reading-while-listening and graphics for learning directly taught facts, but underscore the difficulty in integrating semantic knowledge across lessons and languages.